2016
DOI: 10.1186/s12903-016-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a school-based oral health education in preventing untreated dental caries and increasing knowledge, attitude, and practices among adolescents in Bangladesh

Abstract: BackgroundThere is a dearth of published literature that demonstrates the impact and effectiveness of school-based oral health education (OHE) program in Bangladesh and it is one of the most neglected activities in the field of public health. Keeping this in mind, the objectives of this study were to assess the effectiveness of OHE program in: 1) increasing oral health knowledge, attitude, and practices and 2) decreasing the prevalence of untreated dental caries among 6–8 grade school students in Bangladesh.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
125
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 29 publications
30
125
1
12
Order By: Relevance
“…Haque et al reported that the level of attitude and knowledge scores was higher and improved ( P < .001) at the follow‐up vs the baseline group (75.9% vs 19.3%, 57.8% vs 14.7%). Further, the frequency of cleaning teeth 3 times or more per day was significantly improved ( P < .001) in the follow‐up group vs baseline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haque et al reported that the level of attitude and knowledge scores was higher and improved ( P < .001) at the follow‐up vs the baseline group (75.9% vs 19.3%, 57.8% vs 14.7%). Further, the frequency of cleaning teeth 3 times or more per day was significantly improved ( P < .001) in the follow‐up group vs baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Oral health education aims to improve overall knowledge, which may lead to the adoption of favourable oral health behaviours that in return lowers oral health morbidity . However, lack of health education and insufficient preventive measures have led to a high prevalence of oral health issues, especially in LMICs . Oral health promotion interventions focusing on clinical oral health are important for the maintenance of healthy dentition and periodontium; this could then reduce the requirement for emergency dental treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Oral health education has been considered to be an important principle of dental health services for several years and successful in many developing and developed countries . Dental health education can be delivered to groups of people in various settings like schools, workplaces and even the residential for older adults …”
Section: Introductionmentioning
confidence: 99%
“…12 Oral health education has been considered to be an important principle of dental health services for several years 8,13 and successful in many developing and developed countries. 4 Dental health education can be delivered to groups of people in various settings like schools, workplaces and even the residential for older adults. 8,14 Evaluating the effectiveness of various types and combinations of education 11 with behaviour modification techniques is an essential part of dental health intervention.…”
mentioning
confidence: 99%
“…Şimdilerde öğret-menlerin okul temelli dental eğitimde potansiyel bir rol oynadığı uluslararası olarak kabul görmek-tedir, bu nedenle öğretmenlerin ağız ve diş sağlığı hakkındaki bilgi düzeyi kayda değer bir öneme sahiptir. [81][82][83][84][85][86][87][88][89][90] …”
Section: Eçç'ni̇n öNlenmesi̇nde Okul Temelli̇ Dental Eği̇ti̇munclassified